Literacy Affects Spoken Language in a Non-Linguistic Task: An ERP Study - Perre, Laetitia; Bertrand, Daisy; Ziegler, Johannes (Frontiers in Psychology, 2011)
It is now commonly accepted that orthographic information influences spoken word recognition in a variety of laboratory tasks (lexical decision, semantic categorization, gender decision). However, it remains a hotly debated issue whether or not orthography would influence normal word perception in passive listening. That is, the argument has been made that orthography might only be activated in laboratory tasks that require lexical or semantic access in some form or another. It is possible that these rather “unnatural” tasks invite participants to use orthographic information in a strategic way to improve task performance. To put the strategy account to rest, we conducted an event-related brain potential (ERP) study, in which participants were asked to detect a 500ms-long noise burst that appeared on 25% of the trials (Go trials). In the NoGo trials, we presented spoken words that were orthographically consistent or inconsistent. Thus, lexical and/or semantic processing was not required in this task and there was no strategic benefit in computing orthography to perform this task. Nevertheless, despite the non-linguistic nature of the task, we replicated the consistency effect that has been previously reported in lexical decision and semantic tasks (i.e., inconsistent words produce more negative ERPs than consistent words as early as 300 ms after the onset of the spoken word).. These results clearly suggest that orthography automatically influences word perception in normal listening even if there is no strategic benefit to do so. The results are explained in terms of orthographic restructuring of phonological representations.